Smart Urban Water Management: Integrating AI and IoT for Optimization and Waste Reduction - Das, Ritankar (Optimality, 2024)
The management of water resources is becoming more intricate as urban areas grow and the demand for water increases. This study examines how the combination of Artificial Intelligence (AI) and Internet of Things (IoT) technologies can deliver innovative solutions for smart city water management. IoT devices facilitate the real-time monitoring of water systems, whereas AI aids in analyzing extensive data for tasks such as predictive maintenance, leak detection, and demand forecasting. By enhancing water distribution efficiency and reducing waste, AI and IoT present groundbreaking opportunities in urban water resource management. The study outlines the technical frameworks, primary applications, challenges, and future prospects of AI and IoT within this domain.